2018
DOI: 10.1161/circulationaha.117.030114
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Myocardial Injury After Noncardiac Surgery

Abstract: 1 ORIGINAL RESEARCH ARTICLE ORIGINAL RESEARCH ARTICLEEditorial, see p XXX BACKGROUND: Perioperative myocardial injury (PMI) seems to be a contributor to mortality after noncardiac surgery. Because the vast majority of PMIs are asymptomatic, PMI usually is missed in the absence of systematic screening. METHODS:We performed a prospective diagnostic study enrolling consecutive patients undergoing noncardiac surgery who had a planned postoperative stay of ≥24 hours and were considered at increased cardiovascular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
338
4
26

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(379 citation statements)
references
References 25 publications
11
338
4
26
Order By: Relevance
“…A troponin value of 61 ng/L was the most appropriate cutoff to predict 30‐day mortality with a sensitivity of 57.2% (95% CI, 27.6%‐86.6%), specificity of 90% (95% CI, 85.4%‐94.5%), negative predictive value of 96.6% (95% CI, 93.6%‐99.6%), and positive predictive value of 29.6% (95% CI, 10.6%‐48.7%). Remarkably, different troponin thresholds proposed for the diagnosis of perioperative myocardial injury published elsewhere (except hsTnT >65 ng/L) failed to show any discriminant capacity (Supporting Table 1).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…A troponin value of 61 ng/L was the most appropriate cutoff to predict 30‐day mortality with a sensitivity of 57.2% (95% CI, 27.6%‐86.6%), specificity of 90% (95% CI, 85.4%‐94.5%), negative predictive value of 96.6% (95% CI, 93.6%‐99.6%), and positive predictive value of 29.6% (95% CI, 10.6%‐48.7%). Remarkably, different troponin thresholds proposed for the diagnosis of perioperative myocardial injury published elsewhere (except hsTnT >65 ng/L) failed to show any discriminant capacity (Supporting Table 1).…”
Section: Resultsmentioning
confidence: 91%
“…Recent studies have suggested that patients with cirrhosis with enhanced systolic function show a paradoxical response under hemodynamically stressful situations, suffering an important decrease in contractility indicative of a marked decrease in contractile reserve . On the other hand, several studies have indicated that even subtle elevations of troponin levels are clinically relevant and have prognostic implications in different surgical contexts …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients at elevated risk for cardiovascular complications are prone to perioperative adverse cardiac events, such as myocardial injury after non-cardiac surgery (MINS) (1) and face higher perioperative mortality (1)(2)(3)(4). Atherosclerosis and its complications are driven by systemic inflammation (5), however the mechanisms underlying perioperative cardiovascular complications are not fully understood (6,7).…”
Section: Introductionmentioning
confidence: 99%